생물반응공정에 대한 고액분리조로서 부상공정의 적용성 평가 - 정종민; 김윤중; 조강우; 이상협; 홍석원; 정태학 (대한상하수도학회, 2008)
An experimental study was carried out to evaluate the potential of flotation process for the secondary clarifier of an activated sludge process. Flotation techniques, applied in this study, include electrofloation (EF) which generated fine bubbles smaller than 35 ？m in average and diffuser flotation (DF) which generated fine bubbles smaller than 55 ？m in average. The batch experiments were done with activated sludge displaying various characteristics. It was shown that the efficiency of solids/liquid separation was reduced as the diluted sludge volume index (DSVI30) of activated sludge increased. The dependency, however, gradually decreased as the gas to solids (G/S) ratio increased. Thickening efficiency of EF was more than 2∼10 times and DF process was more than 1.5∼5 times as compared with gravity sedimentation (GS). Stable sludge blanket was maintained regardless of sludge settleability when the G/S ratio was 0.019 in the EF. On the other hand, Serious deterioration in the sludge blanket was observed in the DF depends on G/S ratio and sludge settleability. And For EF and DF, the suspended solids concentration of effluent was not nearly influenced on settleability of activated sludge and more clear than GS. A biological nutrient removal (BNR) process, combined with EF as a secondary clarifier was operated for three months. The mean MLSS (mixed liquid suspended solids) concentration in the reactor and mean solids concentration of return sludge were estimated to be 5,340 mg/L and 16,770 mg/L, respectively. The water quality of effluent was considerably stable and low value was accomplished, that was, standard suspended solids concentration 0.07 ± 0.51 mg/L and standard turbidity 1.44 ± 0.56 NTU. The EF could be applicable for enhancement of efficiency of activated sludge system as well as improvement of the water quality of effluent.